The Effectiveness of I-CARE-based Self-Efficacy Nurses Training for the Development of Organizational Commitment at Panti Rapih Hospital Yogyakarta - Sihaloho, Martha; Susilo, Wilhelmus Hary; Dedi, Blacius (STIKep PPNI Jawa Barat, 2024)
Aims: This research aims to analyze the effectiveness of I-CARE-based self-efficacy nurses training for the development of organizational commitment at Panti Rapih Hospital Yogyakarta. Methods: The research has been designed as a quasi-experiment one group pretest and posttest. The respondents are 143 nurses, mostly from D3 (associate degree) in Nursing (82.5%), female (88.1%), and young adult age or generation X (48.8%). Most of them have also been working for 6-15 years (51.8%). Ordinal regression discrimination test and SEM Smart PLS.4 with path analysis were also conducted. The data is analyzed by using software SPSS.25 and Wilcoxon pretest and posttest on I-CARE-based self-efficacy training and organizational commitment. Results: I-CARE-based self-efficacy has been found “high” (55.9%). Nurses’ organizational commitment is “high” (77.6%), “average” (18.2%) and “low” (4.2%). It is also found that I-CARE-based self-efficacy does not have a significant relation with organizational commitment, which P value is >0.005. The variables like age, gender and length of working have also been insignificant to the enhancement of organizational commitment, which P value is >0.005. The level of education gives a significant influence to organizational commitment, which P value is 0.02 (<0.005). The enhancement of education level will reinforce organizational commitment. Conclusion: I-CARE-based self-efficacy training is effective in enhancing organizational commitment, but for significant impact, it should be supported by a higher level of education. This research recommends increasing formal education levels to enhance staff organizational commitment.